PENYUSUNAN INSTRUMEN ASESMEN KETUNTASAN MINIMUM NUMERASI BAGI GURU SEKOLAH DASAR - Dian Kusmaharti; Feny Rita Fiantika; Susi Hermin Rusminati; Via Yustitia (Jurnal Abdimas Bina Bangsa, 2022)
The competence of elementary school teachers in the preparation of a minimum numeracy completeness assessment needs to be a concern. Most of the teachers at SDN Sumur Welut III Surabaya, the teachers do not have experience in preparing numeration questions. The purpose of this community service is to improve the competence of elementary school teachers in compiling a minimum numeracy completeness assessment instrument. The intended target is the teacher of SDN Sumur Welut III Surabaya. This activity is carried out in the form of training and workshops, starting with material presentations, discussions, and workshops with lecturer assistance during group work. The results of the activity show that: (1) there is an increase in the understanding and skills of teachers in compiling the minimum numeracy completeness assessment instrument; (2) The participant's response showed a positive response